2019
DOI: 10.1002/qj.3538
|View full text |Cite
|
Sign up to set email alerts
|

A case‐study of land–atmosphere coupling during monsoon onset in northern India

Abstract: This article presents a land–atmosphere case‐study for a single day during monsoon onset, incorporating data from a research aircraft, satellite products and model outputs. The unique aircraft observations reveal temperature and humidity contrasts of up to 5 K and 4 g/kg in the planetary boundary layer induced by spatial variations in soil moisture. Both antecedent rain and irrigation were found to be drivers of this atmospheric variability. There is also evidence of soil moisture‐induced mesoscale circulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…More details of the NCUM‐R land–atmosphere coupling during the campaign period is discussed in the recent work of Barton et al . (). For the active monsoon conditions (Figure c), the profile over the continental location (Lucknow) from the model is found to contain stronger updraughts; specifically Diag gives a maximum updraught in the mid‐levels, which is missing in the PC2 simulations.…”
Section: Evaluation Of Ncum‐r and Its Sensitivity To Cloud Parametrizmentioning
confidence: 97%
“…More details of the NCUM‐R land–atmosphere coupling during the campaign period is discussed in the recent work of Barton et al . (). For the active monsoon conditions (Figure c), the profile over the continental location (Lucknow) from the model is found to contain stronger updraughts; specifically Diag gives a maximum updraught in the mid‐levels, which is missing in the PC2 simulations.…”
Section: Evaluation Of Ncum‐r and Its Sensitivity To Cloud Parametrizmentioning
confidence: 97%
“…These demonstrate the importance of agricultural practices as well as meteorology in determining the partition between sensible-and latent-heat fluxes. At smaller scales, Barton et al (2020) have demonstrated that gradients in soil moisture, whether caused by antecedent rainfall or irrigation practices, lead to mesoscale convergence patterns that can initiate storms. Finally, using the IIT Kanpur flux tower observations, Chakraborty et al (2019) found that the NOAH land-surface model significantly underestimates the latent-heat flux over the region during the monsoon onset period, which was partly addressed by improving the vegetation parametrization in the model.…”
Section: Emerging Resultsmentioning
confidence: 99%
“…At smaller scales, Barton et al . () have demonstrated that gradients in soil moisture, whether caused by antecedent rainfall or irrigation practices, lead to mesoscale convergence patterns that can initiate storms. Finally, using the IIT Kanpur flux tower observations, Chakraborty et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other work published so far in the Special Collection includes a description of the modelling and forecast tools employed in guiding the flight missions (Martin et al ., 2020) and an evaluation of convective‐scale model performance in comparison to flight observations (Jayakumar et al ., 2020). There is a proof‐of‐concept of the importance of mesoscale soil moisture gradients over northern India in initiating convection, based on flight observations and modelling (Barton et al ., 2020), and the new identification of distinct regimes of onshore and offshore convection around the Western Ghats, based on flight and flux‐tower measurements (Fletcher et al ., 2020) which could lead to new insights in forecasting.…”
mentioning
confidence: 99%